The importance of corrosion resistance test of cannulas in the quality control of hypodermic needles - Michele Feitoza-Silva; Carolina Mesquita de Carvalho; Lívia Bretas Bittencourt; Katia Christina Leandro; André Luis Gemal (Universidade de São Paulo, 2019)
According to Anvisa risk rating, hypodermic needles offer medium risk to the user's health. This study discussed the importance of the corrosion resistance test in tubes of hypodermic needles, in the product quality control. A review of cannulas of hypodermic needles was carried out according to ISO 9626:2003 and 9259:1997 ABNT NBR. For the results evaluation, a scale which classifies the extent of corrosion was adjusted. 174 samples of PNI needles from 17 States and 9 different record holders were analyzed. According to the methodology of ISO 9626:2003, 100% of the samples were considered satisfactory. However, in accordance with the methodology of ISO 9259:1997, 97.1% of the samples were rejected. Irregularities can lead to impairment of product quality, resulting in risks to the consumer's health. Since 2011 the product has undergone certification, so it is necessary to reflect on the importance of corrosion resistance testing and mandatory certification for health monitoring.